2018
DOI: 10.1016/j.bmcl.2018.04.055
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of evocalcet, a next-generation calcium-sensing receptor agonist for the treatment of hyperparathyroidism

Abstract: The calcium-sensing receptor (CaSR) plays an important role in sensing extracellular calcium ions and regulating parathyroid hormone secretion by parathyroid gland cells, and the receptor is a suitable target for the treatment of hyperparathyroidism. Cinacalcet hydrochloride is a representative CaSR agonist which widely used for the hyperparathyroidism. However, it has several issues to clinical use, such as nausea/vomiting and strong inhibition of CYP2D6. We tried to improve these issues of cinacalcet for a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…The aforementioned modifications resulted in a phenylacetic acid compound that exhibited greatly improved bioavailability, demonstrating 84% bioavailability in rats compared with 1–2% for cinacalcet . In humans, a mass balance study showed high bioavailability (62.7%), which was a significant improvement compared with cinacalcet (5–30%) (unpublished data, Kyowa Kirin Co., Ltd.).…”
Section: Evocalcetmentioning
confidence: 97%
See 2 more Smart Citations
“…The aforementioned modifications resulted in a phenylacetic acid compound that exhibited greatly improved bioavailability, demonstrating 84% bioavailability in rats compared with 1–2% for cinacalcet . In humans, a mass balance study showed high bioavailability (62.7%), which was a significant improvement compared with cinacalcet (5–30%) (unpublished data, Kyowa Kirin Co., Ltd.).…”
Section: Evocalcetmentioning
confidence: 97%
“…To develop evocalcet, cinacalcet analogs were generated to reduce the off‐target effects of cinacalcet, which may be responsible for the upper GI disorders. The addition of a five‐membered ring (pyrrolidine ring) to the structure of cinacalcet was found to decrease its affinity for and inhibitory effect on CYP2D6 by hindering the basic amine surroundings . Modifications to improve bioavailability included adjustments to the configuration of the pyrrolidine ring and to the size of the ring structure, as well as optimization of the carboxylic acid position .…”
Section: Evocalcetmentioning
confidence: 99%
See 1 more Smart Citation
“…Cinacalcet, a calcimimetic agent that suppresses PTH by direct action on the parathyroid CaSR, was approved in western countries in 2004 and in Japan in 2008 . A second calcimimetic, an intravenous formulation of etelcalcetide (February 2017) , and a third, evocalcet (May 2018) became clinically available in Japan ahead of all other countries. At the same time, the importance of P control has been recognized for mortality, cardiovascular calcification, and SHPT outcomes, which has led to development of phosphate binders (Fig.…”
Section: Treatment Of Shptmentioning
confidence: 99%
“…A new oral calcimimetic, evocalcet (65)(66)(67)(68)(69), has also been developed and was approved in Japan in April 2018. In a controlled trial with cinacalcet, evocalcet had noninferiority for PTH inhibition.…”
Section: Calcimimeticsmentioning
confidence: 99%